NFκB activation and stimulation of chemokine production in normal human macrophages by the gadolinium-based magnetic resonance contrast agent Omniscan: possible role in the pathogenesis of nephrogenic systemic fibrosis. Issue 11 (18th October 2010) - Galdo, Francesco Del; Wermuth, Peter J; Addya, Sankar; Fortina, Paolo; Jimenez, Sergio A
Abstract : Objective: Nephrogenic systemic fibrosis (NSF) is a generalised fibrotic disorder occurring in certain individuals with renal insufficiency exposed to gadolinium-based contrast agents (GdBCA) for MRI. Histopathological examination of affected tissues shows increased numbers of activated macrophages. To elucidate the mechanisms responsible for macrophage activation, the effects of the GdBCA Omniscan on normal human macrophage global gene expression, chemokine production and nuclear factor κB (NFκB) activation was examined. Methods: Normal human monocyte-derived macrophages were incubated with Omniscan (50 mM) and their gene expression analysed by microarrays and real-time PCR. Macrophage chemokine production was assayed by multiplex ELISA. NFκB activation was assessed by NFκB nuclear localisation and quantitation of intracellular levels of inducible nitric oxide synthase (iNOS) protein. A specific cell-permeable NFκB peptide inhibitor was used to abrogate NFκB stimulation of chemokine and iNOS protein levels. CCL8/MCP-2 in affected skin of patients with NSF was examined by indirect immunofluorescence. Results: Omniscan caused a profound change in the transcriptome of differentiated human normal macrophages in vitro, including a large increase in the expression of genes encoding CC and CXC chemokines. It induced rapid nuclear localisation of NFκB and stimulation of iNOS protein levels and chemokine production which were blocked by an NFκB inhibitory peptide. CCL8/MCP-2, the most upregulated chemokine following in vitro macrophage exposure to Omniscan, was strongly increased in NSF-affected skin. Conclusion: The GdBCA Omniscan induces potent stimulation of macrophage gene expression, NFκB activation and increased NFκB-mediated production of CC and CXC chemokines and iNOS. These alterations may play a crucial role in the pathogenesis of NSF.